#TITLE_ALTERNATIVE# - BAYU KRISTIAN NIM: 13204156, ADE
This paper presents busbar protection techniques using wavelet packet transform (WPT). The proposed techniques contain 4 steps. In first step, mode transform, called Clarke Transform, is used to transform fault current signal into mode current signal, i.e. ground mode and aerial mode. In second step, those mode signals are transformed by WPT to extract properties of the signal to obtain wavelet transform coeffisient (WTC). Then in third step, WTC is observed to obtain Signal Differential Coefficient (SDC). Finally, in fourth step, Trip signal is generated from SDC using certain equation. This techniques is able to detect and differentiate internal fault and external fault. The CT error and ratio-mismatch problem do not have any impact on the proposed WPT-based scheme. ATP simulations and MATLAB are used to test and validate the proposed technique for model-power-system faults..